2022
DOI: 10.1542/peds.2022-057092e
|View full text |Cite
|
Sign up to set email alerts
|

Early Enteral Feeding for Preterm or Low Birth Weight Infants: a Systematic Review and Meta-analysis

Abstract: CONTEXT Early enteral feeding has been associated with adverse outcomes such as necrotizing enterocolitis in preterm and low birth weight infants. OBJECTIVES To assess effects of early enteral feeding initiation within the first days after birth compared to delayed initiation. DATA SOURCES Medline, Scopus, Web of Science, CINAHL from inception to June 30, 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Regarding factors determining the weight gain status of the preterm neonates, the current study showed that the delayed start of enteral feeding was significantly associated with poor weight gain. Preterm neonates who started enteral feeding after 24 h were almost four times more likely to have poor weight gain compared to those who started enteral feeding within 24 h. This result was supported by studies conducted in the US ( 21 ), Romania ( 22 ), India ( 23 ), Tanzania ( 14 ), and Uganda ( 5 ) and might be caused by the delayed start of enteral feeding possibly influencing the achievement of the full daily requirement and affecting the weight gain status.…”
Section: Discussionsupporting
confidence: 60%
“…Regarding factors determining the weight gain status of the preterm neonates, the current study showed that the delayed start of enteral feeding was significantly associated with poor weight gain. Preterm neonates who started enteral feeding after 24 h were almost four times more likely to have poor weight gain compared to those who started enteral feeding within 24 h. This result was supported by studies conducted in the US ( 21 ), Romania ( 22 ), India ( 23 ), Tanzania ( 14 ), and Uganda ( 5 ) and might be caused by the delayed start of enteral feeding possibly influencing the achievement of the full daily requirement and affecting the weight gain status.…”
Section: Discussionsupporting
confidence: 60%
“…This was based on evidence of moderate benefits of decreased mortality and length of hospital stay (moderate certainty), and decreased intra-ventricular haemorrhage (very low certainty) in trials (n = 14) of infants <37 weeks gestation or <2.5 kg birth weight, including 6 trials in infants <32 weeks <1.5 kg; there was no evidence of harms. 22 Infants who are able to breastfeed should be put to the breast as soon as possible after birth; infants who are unable to breastfeed should be given expressed mother’s own milk whenever possible and put to breast for non-nutritive sucking. The guideline emphasised the need for careful consideration in applying these recommendations to unstable babies; initiation of enteral feeding in unstable babies should be based on clinical judgement.…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen new systematic reviews were commissioned to assess topics not addressed in existing reviews and 21 additional existing systematic reviews and meta analyses were assessed by the GDG ( Supplementary Table S2 ). 7 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 The quality of the scientific evidence for each intervention was graded using the Grading of Recommendations Assessment, Development and Evaluation (GRADE), 40 and evidence was categorised as high, moderate, low and very low certainty. The Confidence in the Evidence from Reviews of Qualitative research (CERQual) 41 approach was used for qualitative evidence.…”
Section: Methodsmentioning
confidence: 99%
“…Our findings suggest that postnatal growth patterns of very preterm infants based on measurements recorded between 2010 through 2020 are similar to the growth pattern reported by Ehrenkranz et al in 1999, and are different from the 2013 Fenton growth charts. Despite decades of work directed at monitoring and optimizing the growth of preterm infants 16 22 , postnatal weight, length, and head circumference growth do not approximate intrauterine growth. The intrauterine and postnatal growth patterns diverge from birth and remain different throughout the assessment period.…”
Section: Discussionmentioning
confidence: 99%